GOALS AND OBJECTIVES OF FINANCIAL SUPPORT OF THE POULTRY SECTOR IN THE DEVELOPMENT STRATEGY OF THE NEW UZBEKISTAN - Kutbitdinova Moxigul Inoyatova; Bashirova Yulduzxon Jahongirovna (Scholar Express Journals, 2023)
The development of the poultry industry in the country in this direction focuses on such topical issues as the continuous supply of the country's population with high-quality poultry and egg products, an increase in sales of domestic poultry products in the domestic and foreign markets, the widespread introduction of modern production methods, the creation of a value chain , effective use of modern information and communication technologies
Keywords: poultry clusters; increase in real income; increase in efficiency